Occasional, extravagant, 'remote' variants. Giudici's latest variants in 'Tevere. (Prassi Ecdotiche della Modernità Letteraria, 2021)
The present article takes into consideration, as a singular and noteworthy case, three variants of a prose by Giovanni Giudici, 'Tevere', the peculiarity of which consists in having been formulated occasionally and at a distance - not only of time - from the relevant text; of having been, therefore, dictated by the author not in the context of a revision or an overall rewriting of the original, but in the context of a self-quotation extrapolated from another's writing; a quotation that, further on, has been dictated by the author in the context of a self-citation of the original.They were, therefore, dictated by the author not in the context of a revision or an overall rewriting of the original, but rather in the context of a self-quotation extrapolated from someone else's writing; a quotation which, further modified, was later inserted by Giudici himself in a new, different narrative text.